If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + 3) + 5(x + -7) = 41 Reorder the terms: 2(3 + x) + 5(x + -7) = 41 (3 * 2 + x * 2) + 5(x + -7) = 41 (6 + 2x) + 5(x + -7) = 41 Reorder the terms: 6 + 2x + 5(-7 + x) = 41 6 + 2x + (-7 * 5 + x * 5) = 41 6 + 2x + (-35 + 5x) = 41 Reorder the terms: 6 + -35 + 2x + 5x = 41 Combine like terms: 6 + -35 = -29 -29 + 2x + 5x = 41 Combine like terms: 2x + 5x = 7x -29 + 7x = 41 Solving -29 + 7x = 41 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '29' to each side of the equation. -29 + 29 + 7x = 41 + 29 Combine like terms: -29 + 29 = 0 0 + 7x = 41 + 29 7x = 41 + 29 Combine like terms: 41 + 29 = 70 7x = 70 Divide each side by '7'. x = 10 Simplifying x = 10
| (w+5)*(w-3)=0 | | 25-5d=d | | -30(-5)= | | 2(-4)(-6)= | | (-14)2= | | 3x+5(x-7)=41 | | (6)(-8)= | | 0.80x+0.50(8-x)=.10(-101) | | 2g-2+4g-9= | | Y=X[X-4] | | -21=x+10 | | (-6)(-9)= | | X-19=-43 | | 90+2x+x+15=180 | | (-2)(8)= | | 2x-9y-4=0 | | 3x^2+2x=12 | | 4-2x=5-x-1 | | .05d-3d+5=0 | | X+12+x=44 | | -4[X+2]=3[2X+1] | | 2(2x-3)=x+3(x-6) | | 6(x-2)=4-2x | | 4x^2+6x-8x^2=5 | | y=-1.3x-2 | | 13-2x=25 | | c^2=196 | | -5(a+6)=2(3a+8) | | 64=x+32 | | 6x^2+27x=15 | | 6x-7=-4x+4 | | 2(p-q)=r |